156k views
1 vote
Please anyone help me

Please anyone help me-example-1

1 Answer

2 votes

Answer: The answer is x=
(-3-√(65) )/(4),
(-3+√(65) )/(4)

Explanation:

1) You can solve a situation like
ax^2+bx+c=0 using the quadratic formula


x=-b±
√(b^2-4ac) / 2a

2) Apply that to the problem and we get x= -3±
√(3^2-4*2*(-7))/2*2

3) Solve what's inside the square root and what's at the denominator --> x=-3±
√(65)/4

4) separate the solutions --->
x=(-3+√(65))/(4) , (-3-√(65))/(4)

5) Your final solutions are
x=(-3+√(65))/(4) , (-3-√(65))/(4)

User Tessafyi
by
6.7k points